Identification of hsa_circ_0018905 as a New Potential Biomarker for Multiple Sclerosis - Valeria Lodde; Ignazio Roberto Zarbo; Gabriele Farina; Aurora Masia; Paolo Solla; Ilaria Campesi; Giuseppe Delogu; Maria Rosaria Muroni; Dimitrios Tsitsipatis; Myriam Gorospe; Matteo Floris; Maria Laura Idda (Cells)
Multiple sclerosis (MS) is a demyelinating autoimmune disease characterized by early onset, for which the interaction of genetic and environmental factors is crucial. Dysregulation of the immune system as well as myelinization-de-myelinization has been shown to correlate with changes in RNA, including non-coding RNAs. Recently, circular RNAs (circRNAs) have emerged as a key player in the complex network of gene dysregulation associated with MS. Despite several efforts, the mechanisms driving circRNA regulation and dysregulation in MS still need to be properly elucidated. Here, we explore the panorama of circRNA expression in PBMCs purified from five newly diagnosed MS patients and five healthy controls (HCs) using the Arraystar Human circRNAs microarray. Experimental validation was then carried out in a validation cohort, and a possible correlation with disease severity was tested. We identified 64 differentially expressed circRNAs, 53 of which were downregulated in PBMCs purified from MS compared to the HCs. The discovery dataset was subsequently validated using qRT-PCR with an independent cohort of 20 RRMS patients and 20 HCs. We validated seven circRNAs differentially expressed in the RRMS group versus the HC group. hsa_circ_0000518, hsa_circ_0000517, hsa_circ_0000514, and hsa_circ_0000511 were significantly upregulated in the MS group, while hsa_circ_0018905, hsa_circ_0048764, and hsa_circ_0003445 were significantly downregulated; Among them, the expression level of hsa_circ_0018905 was significantly decreased in patients showing a higher level of disability and in progressive forms of MS. We described the circRNAs expression profile of PBMCs in newly diagnosed MS patients and proposed hsa_circ_0018905 as potential MS biomarker.